Ngữ nghĩa học - Kearns, Kate (Palgrave Macmillan, 2011)
"This introductory textbook assumes no prior knowledge and covers a wide range of core topics in formal semantics. Now thoroughly updated, the second edition features new chapters on semantic composition, type theory and the lambda calculus, as well as a revised discussion of Pragmatics and a variety of new exercises"--Provided by publisher.; Machine generated contents note: -- Introduction -- First Order Logic -- The Logical Quantifiers -- Formal Composition -- Modality and Possible Worlds -- Generalized Quantifiers -- Referencial Opacity -- Aktionsarten: Aspectual Classes of Events -- Tense and Aspect -- Thematic Roles and Lexical Conceptual Structure -- Events -- Bibliography -- Index.; Includes bibliographical references and index